A Phenomenological Investigation of Senior High School Learners with Low English Language Proficiency - Ronald D. Romero; Glen P. Cortezano; Karen A. Manaig; Alberto D. Yazon; John Frederick B. Tesoro (Journal of English as A Foreign Language Teaching and Research, 2023)
Several studies have been conducted locally to internationally, revealing the deterioration of the English proficiency of Filipinos, especially high school learners. Still, only a few have determined the causes of why it is constantly happening. Hence, this phenomenological study investigated the experiences of public senior high school learners under the Technical-Vocational-Livelihood (TVL) track with low English language proficiency to identify various reasons why they are still encountering such problems in English and create an intervention program for them to enhance their skills. Specifically, this research utilized transcendental phenomenology and applied triangulation of the three methods: observations, field notes, and interviews. Also, the researcher followed Colaizzi's Method of Phenomenology, as presented in Morrow, Rodriguez, and King (2015), in analyzing and interpreting the data gathered from the individual interviews. Based on the testimonies and shared experiences of the participants, they knew they had difficulty learning English as early as elementary, while others were during their Junior High School (JHS) and Senior High School (SHS) years. In this study, the following themes emerged: traumatic experience, language anxiety, external factors, learners' motivation and interest, self-awareness, academic performance, learning styles and strategies, and the essence and value of the English language. The researcher recommends that teachers address the learners' problems to enhance their English proficiency and academic performance. It was also recommended for future researchers to investigate the teachers' perspective and assessment based on their experience since they are considered one factor in the learners' low English language proficiency.